2017
DOI: 10.1055/s-0043-106437
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-524-5p Functions as a Tumor Suppressor in a Human Pituitary Tumor-Derived Cell Line

Abstract: Clinical nonfunctional pituitary adenomas (NFAs) account for about 40% of pituitary adenomas with almost no clinically relevant hormonal symptoms. Increasing evidence shows that many microRNAs are involved in the development and progression of pituitary adenomas. MicroRNA-524-5p (miR-524-5p) has been reported to cause characteristic alterations in various tumors. However, the functional importance of miR-524-5p in NFAs remains unknown. The aim of this study was to explore the effects of overexpressing miR-524-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
12
0
2
Order By: Relevance
“…These miRNAs decreased Wee1 protein expression and inhibited HeLa cell proliferation [71]. Studies conducted by our research group have found overexpressing miR-524-5p [72] downregulated PTTG1-binding factor (PBF) expression and regulated the biological properties of PDFS(pituitary tumor-derived folliculostellate cell). This could be noted as a potential therapeutic target for non-functioning pituitary adenomas.…”
Section: Mirnas In Non-functioning Pituitary Adenomasmentioning
confidence: 99%
“…These miRNAs decreased Wee1 protein expression and inhibited HeLa cell proliferation [71]. Studies conducted by our research group have found overexpressing miR-524-5p [72] downregulated PTTG1-binding factor (PBF) expression and regulated the biological properties of PDFS(pituitary tumor-derived folliculostellate cell). This could be noted as a potential therapeutic target for non-functioning pituitary adenomas.…”
Section: Mirnas In Non-functioning Pituitary Adenomasmentioning
confidence: 99%
“…Whether or not other miRNAs regulate PA pathogenesis by similarly targeting tumor oncogenes or tumor suppressor genes needs further study. A brief summary of differentially expressed miRNAs in PAs with their targets and implications is tabulated in Table 1 [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: The Current State Of Mirna Research In Pasmentioning
confidence: 99%
“…Indeed, in recent years, mice xenografts have been widely used to characterize the responses to drugs currently prescribed for these pathologies as lanreotide (Ning et al 2009), thiazolidinediones (Mannelli et al 2010), bromocriptine and/or cabergoline (Lin et al 2017) or to alternative therapies such as metformin , histone deacetylase inhibitor SAHA (Lu et al 2017), Liquiritigenin (Wang et al 2014), Triptolide (Li et al 2017) or Bafilomycin A1 (McSheehy et al 2003), which have been shown to exhibit antitumoral roles in these pathologies. Likewise, PAs xenograft models have also been used to characterize the function of different pathways, genes and relevant mutations in several types of PAs, as Fgfr4 in intracranial xenograft mouse models (Ezzat et al 2006, Jalali et al 2016, inactivating mutations of Pit-1 (Roche et al 2012), overexpression of Lrig1 (Cheng et al 2016) or Meg3 (Chunharojrith et al 2015), persistent activation of the Ras/MAPK pathway (Booth et al 2014), antitumoral actions of miR-524-5p (Zhen et al 2017) and role of RSUME in PTTG protein stabilization (Fuertes et al 2018). Finally, PDX models have been sparsely implemented in the case of PAs.…”
Section: Models Of Pituitary Tumorsmentioning
confidence: 99%